(untitled) (International Journal of Studies in Nursing, 2025)
Announcement of Withdrawal The editorial board announced this article has been withdrawn on July 22, 2025. If you have any further question, please contact us at: ijsn@julypress.com Article Title: Leveraging Generative AI for Inclusive Online Friendship Education: Integrating Easy-to- Read Guidelines for Enhanced Accessibility Author/s: Han Chun Huang & Hsiao Wen Chuang Journal Title: International Journal of Studies in Nursing ISSN 2424-9653 E-ISSN 2529-7317 Volume and Number: Vol. 10, No. 1, 2025 Pages: 31-52 DOI: 10.20849/ijsn.v10i1.1502